Study of application of SCM technique in optical FM non-coherent detection system - Lung, James Lam. (2009)
Much attentions have been paid to the Subcarrier Multiplexing technique in optical communication systems in recent years. Comparing with most of the existing systems using optical intensity modulation and time division multiplexing method, systems employing SCM technique allows many channels of signals of different nature (analog or digital) to be transmitted over a single optical channel simultaneously.